Complete chloroplast genome of Actaea heracleifolia (Kom.) J. Compton - Park, Inkyu (Mitochondrial DNA B Resour, 2018)
Dried rhizomes of Actaea heracleifolia, used as a traditional Korean herbal medicine, are frequently adulterated with other plant species. For accurate species identification, we sequenced the complete chloroplast genome of A. heracleifolia using Illumina MiSeq. A. heracleifolia harbours a 159,578 bp chloroplast genome comprising a large single-copy region (88,770 bp), small single-copy region (18,070 bp) and two inverted repeat (IR) regions (IRa and IRb; each 26,519 bp). The chloroplast genome contains 112 unique genes, including 78 protein-coding genes, 4 ribosomal RNA genes, and 30 transfer RNA genes. Phylogenetic analysis revealed that A. heracleifolia was closely related to Gymnaconitum gymnandrum.